Nitrogen Balance and Uric Acid Excretion in Lohmann-Brown Hens Fed Diets with Different Crude Protein and Metabolizable Energy Levels - Mădălina CIOARIC (DEGENARO); Rosalie BĂLĂCEANU; Andrei Tudor KACENCO; Ivona ZĂBAVĂ; Ilinca IOZON; Nicolae DOJANĂ (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Veterinary Medicine)
This study aimed to determine the effect of dietary metabolizable energy (ME) and crude protein (CP) levels on nitrogen excretion and laying performance in laying hens. Four groups of 20-week-old Lohmann hens were fed different ME and CP level diets, expressed as higher (H) or lower (L) versus control: group HME/HCP (2,820 kcal ME/16.7% CP), group HME/LCP (2,820 kcal/14.8% CP), group LME/HCP (2,690 kcal/16.7% CP) and group LME/LCP (2,690 kcal/14.8% CP). The control group was fed a commercial diet (2,754 kcal/15.5% CP). Experimental feeding lasted 12 weeks. Egg production was significantly improved (P=0,015) in HME/HCP group. Feed conversion ratio was significantly lower (P=0.013) in HCP groups versus control). The amount of uric acid excreted by HCP groups was 40% higher versus LCP groups (P=0.000) and excreted uric nitrogen was 24.2% higher in HCP versus LCP groups (P=0.001). HCP groups excreted 0.43 g/cap./day more nitrogen versus LCP groups (P=0.001). HCP groups retained 0.21 g/egg mass/day more nitrogen versus LCP groups. ME-supplements did not significantly modify the amount of nitrogen excretion.  In conclusion, the tested CP diet supplementations increase faecal nitrogen excretion and egg-retained nitrogen in layers. Effect on laying performances depends of CP level and CP/ME ratio in the diet.